2011
DOI: 10.1080/03043797.2011.578244
|View full text |Cite
|
Sign up to set email alerts
|

Remote access laboratories in Australia and Europe

Abstract: Remote access laboratories (RALs) were first developed in 1994 in Australia. The main purposes of developing them are to enable students to do their experiments at their own pace, time and locations, and to enable students and teaching staff to get access to facilities beyond their institutions. Currently, most of the experiments carried out through RALs are heavily biased to electrical, electronic and computer engineering disciplines. RALs in different Australian and European universities were mentioned and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“… Lower-cost access. Online laboratories may help bridge the digital divide by providing students with faster access to experimental learning at a relatively low cost (Burd, Seazzu and Conway, 2009;Flint and Stewart, 2010;Nedungadi and Raman, 2011;Jara et al, 2011;Ku, Ahfock, and Yusaf, 2011). Simulations may be less expensive than experimental hardware, although "little empirical data exists on the actual costs of providing online laboratory access at scale" (Jona et al, 2011).…”
Section: Online Laboratoriesmentioning
confidence: 99%
See 1 more Smart Citation
“… Lower-cost access. Online laboratories may help bridge the digital divide by providing students with faster access to experimental learning at a relatively low cost (Burd, Seazzu and Conway, 2009;Flint and Stewart, 2010;Nedungadi and Raman, 2011;Jara et al, 2011;Ku, Ahfock, and Yusaf, 2011). Simulations may be less expensive than experimental hardware, although "little empirical data exists on the actual costs of providing online laboratory access at scale" (Jona et al, 2011).…”
Section: Online Laboratoriesmentioning
confidence: 99%
“…Online laboratories can enable flexible access to practical experiments, allowing increased study time that is not tied to a specific timetable or location. (Ku, Ahfock, and Yusaf, 2011;Almarshoud, 2011).…”
Section: Online Laboratoriesmentioning
confidence: 99%
“…The modified courses are credited as elective courses at the Berlin Institute of Technology. Ku, Ahfock, and Yusaf (2011) reported that remote access laboratories are being largely developed and used in engineering education in Australia and Europe to allow cost-effective experimentation for students from various institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the equipment can be shared on a national (Lowe et al, 2015;Pradarelli et al, 2009) or global (Bonnaud et al, 2008;Qiao et al, 2010) scale with a breakdown of costs. Moreover, thanks to the different time zone (for example, between Australia and Europe), students worldwide can be run experiments 24/7 (Ku et al, 2011). This international cooperation on technical features needs to accommodate the cultural and social differences to improve teaching effectiveness significantly.…”
Section: Introductionmentioning
confidence: 99%